The Influence of the Discovery Learning Model Assisted by Cultural Diversity Room Image Media on the Learning Outcomes of Pancasila and Citizenship Education of Students - Yulianti, Sofi Eka; Kurniawan, Machful Indra; Harianti, Isnin (EDUCATIO : Journal of Education, 2023)
In the realm of education, the significance of teaching and learning is paramount, with teachers assuming a pivotal role in shaping successful educational outcomes. Learning, viewed as an ongoing lifelong process, is characterized by purposeful endeavors to cultivate individual potential and foster responsible citizenship. Civic education, marked by an emphasis on comprehensive comprehension and skill development, encounters persistent challenges such as the limitations of conventional lecture-based methods that impede effective learning. In response, this study developed a specialized learning module concentrating on two-variable linear equations, employing the ADDIE model. Employing a quantitative experimental research approach, data collection involved comprehensive methods including questionnaires, observations, interviews, and meticulous statistical analysis. The validation process underscored the module's pronounced practicality and engagement, further affirming its viability for implementation. The study's findings, presented earlier, deduced that the integration of the discovery learning model aided by the "bilik" cultural diversity image media significantly influences the learning outcomes of fourth-grade students studying civic education at SD Muhammadiyah 2 Waru. Notably, pretest results averaged at 68.25, while posttest scores displayed an average of 94.7. The t-test calculations confirmed a disparity in the averages, with pretest and posttest increments of 71.17 and 96.7, respectively. These outcomes substantiate the model's efficacy in elevating posttest scores beyond pretest levels, emphasizing its impact on learning outcomes. Consequently, this research offers valuable insights into advancing the effectiveness of civic education through innovative pedagogical strategies.